Plasmodium knowlesi Sub-populations: Genotyping, Temporal Variations and Clinical Manifestations - TING HUEY, HU (Universiti Malaysia Sarawak (UNIMAS), 2021)
Human infections with Plasmodium knowlesi, a simian malaria parasite, have been on a steady rise in Sarawak. In 2014 and 2015, 87.3% of the 2,458 malaria cases in Sarawak were diagnosed as knowlesi malaria. This worrying trend calls for an urgent evaluation of the disease progression of P. knowlesi. Since a prospective study was carried out from 2006-2008 in Kapit, Sarawak, there have been no follow-up studies done on the clinical and laboratory features of knowlesi malaria cases. This paucity of data prevents detailed analysis on the progression and pathology of knowlesi malaria. Hence we conducted a prospective study from 2016-2018 to monitor any changes in clinical and laboratory features of knowlesi malaria by comparing current data with that collected a decade ago with the intention of increasing our knowledge on the pathology of knowlesi malaria. Recently, genome-wide analysis and genotyping of P. knowlesi micro-satellites identified two sub-populations of P. knowlesi in Sarawak and Sabah. Cluster 1 was found mainly associated with long-tailed macaques and Cluster 2 with pig-tailed macaques. We examined whether the two sub-populations contributed to different clinical manifestations and also whether there were any changes in the proportion of the sub-populations over time. Additionally, the current method of genotyping each of the sub-populations involve a single round PCR assay and the development of a hemi-nested PCR assay may prove to be more sensitive. Hemi-nested PCR assays were therefore developed for each sub-population and the Cluster 1 assay was found to be more sensitive and specific but not so for the Cluster 2 assay. Our findings on 420 knowlesi malaria patients at Kapit Hospital showed that there were statistically significant differences between some of the clinical and laboratory parameters of the two sub-populations in both patient groups (Cluster 1 infections had higher proportion of myalgia and abdominal pain; also lower platelet counts, total protein and sodium concentrations, with higher bilirubin and urea concentrations) but the laboratory parameters did not appear to give phenotypic clinical significance. Additionally, Cluster 1 severe cases had significantly lower parasitaemia compared to Cluster 2 severe cases which we postulated to result from parasite-driven factor either through virulence or induction of host response to pathogen. Our findings also showed that Cluster 1 was associated with both peri-domestic (forest fringe) and jungle (interior forest) activities, while Cluster 2 was dominantly associated with jungle exposure. Exposure to these two environments were both age and gender specific, with less women entering the jungle and therefore less likely to acquire Cluster 2 infections. We did not find any significant difference in proportion of the sub-populations between the two patient groups which meant stable ratio between the two sub-populations. Additionally, the temporal change identified in clinical parameters of P. knowlesi such as lower duration of illness, was postulated to be associated with a change in the anti-malarial treatment provided at Kapit Hospital and improved health care accessibility. Based on these results, the increasing number of knowlesi malaria cases over the two time periods was likely to be multifactorial and a result of changes in the environment, macaques or vectors, or from a combination of all three rather than changes in parasite factors. However, the lack of clinical evidence regarding parasite adaptation in our study is not conclusive as we may not have captured the window of change which can stretch to 30 years based on field observation of drug resistance. It will be imperative to undertake future investigation involving in vitro studies such as any difference in life-cycles and preference of red blood cell types to identify the mechanism of pathologies between the two sub-populations as well as vector and macaque hosts’ studies to get a better understanding of this zoonosis.